Five ways of engaging the youth in agriculture - Mammo, Yared (Technical Centre for Agricultural and Rural Cooperation, 2014)
Young peoples' affinity with ICTs and their ability to innovate is the key to moving mAgriculture forward and attracting the youth to the agricultural sector in ACP countries